Periodontal and chronic kidney diseases: A modifiable association - Jabbarzadehkhoei, Foujan; Bakhshandeh, Soheila; Namdari, Mahshid; Pakkhesal, Mina; Khoshnevisan, Mohammad Hossein (Journal of Contemporary Medical Sciences, 2021)
Objectives: The purpose of this study was to assess the relationship between periodontal diseases and CKD duration. Methods: This descriptive cross-sectional study was conducted on referral CKD patients to a teaching hospital in 2017. Two instruments were used for data collection. The first one was a self-reported questionnaire regarding oral health status and patients’ behaviors. The second questionnaire was used for the clinical assessment of oral health status. Results: Out of 192 patients, 46.9% were male and 53.1% female with a mean (SD) age of 51.9 (±15.1) years. The mean duration of CKD was 7.70 (±7.34) years. About 67.7% of patients experienced toothache in the past year. Also, 67.7% had gingival bleeding (BOP), 34.4% had Clinical Attachment Loss (CAL) > 4 mm, and over 50% of patients had a pocket depth (PD) > 4 mm. By controlling the patient’s age, a direct correlation was detected between the duration of CKD and DMFT index (r=0.64, P<0.001). Moreover, the prolongation of the disease period was detected in patients with CAL>4 mm (P=0.02). Likewise, a direct correlation was detected between the duration of CKD and the periodontal index (r=0.48, P<0.001). Conclusion: Given the direct correlation between the periodontal conditions and duration of CKD, regular biannual dental visits are essential for CKD patients. All physicians are encouraged to include regular oral health checkups in the treatment protocol for CKD patients.